COMPAS - Copenhagen Model for Passenger Activity Scheduling - Jovicic, Goran (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
The focus of the paper resides in a description of the proposed structure for a travel demand model for Copenhagen (section 3). The model is named COMPAS, which is an acronym for Copenhagen Model for Passenger Activity Scheduling. COMPAS belongs to the family of activity based demand models that are theoretically superior to the conventional trip based demand models. These two groups of models are compared in a separate section of the article (section 2).